2004
DOI: 10.1007/s10616-005-8306-7
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis and Its Suppression in Hepatocytes Culture

Abstract: In order to achieve the goal of developing extracorporeal liver support devices, it is necessary to optimise bioprocess environment such that viability and function are maximised. Optimising culture medium composition and controlling the constitution of the cellular microenvironment within the bioreactor have for many years been considered vital to achieving these aims. Coupled to this is the need to understand apoptosis, the prime suspect in the demise of animal cultures, including those of hepatocytes. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 65 publications
1
1
0
Order By: Relevance
“…A comparative study of the effects of medium components on hepatocyte functionality in suspension culture highlighted a decrease in ATP/ADP ratio in glucose-free medium (Elaut et al, 2005). Mukwena showed that the absence of glucose inhibited hepatocyte proliferation without any observable effect on cell viability for 96 h culture (Mukwena and Al-Rubeai, 2004). Our results confirm these findings, with culture conditions in beads preserving cell viability higher than 83% after 24 or 48 h of fluidisation.…”
Section: Alginate In Bioartificial Liversupporting
confidence: 84%
“…A comparative study of the effects of medium components on hepatocyte functionality in suspension culture highlighted a decrease in ATP/ADP ratio in glucose-free medium (Elaut et al, 2005). Mukwena showed that the absence of glucose inhibited hepatocyte proliferation without any observable effect on cell viability for 96 h culture (Mukwena and Al-Rubeai, 2004). Our results confirm these findings, with culture conditions in beads preserving cell viability higher than 83% after 24 or 48 h of fluidisation.…”
Section: Alginate In Bioartificial Liversupporting
confidence: 84%
“…In a second approach, we developed a calibration model for the pooled samples analyzed by flow cytometry, which were treated with staurosporine, a protein‐kinase inhibitor and known inducer of apoptosis .…”
Section: Resultsmentioning
confidence: 99%